A Theoretical Review of How Post-Industrialization Shapes the Social-Professional Structure of Modern Society - R. K. Dianov (Дискурс)
Introduction. Today, sociologists and economists observe the rise of atypical employment, accompanied by a gradual shift away from long-term labor contracts. The growth of the gig economy – a contemporary labor system based on temporary and short-term contracts – led to the development of numerous concepts of post-industrial employment. This article examines the theoretical perspectives on the ambiguous effects of changes in the employment institution during the post-industrial era.Methodology and sources. The research builds upon the seminal works of post-industrial society theorists such as D. Bell, A. Toffler, and P.F. Drucker, as well as the concepts of free agents by D.H. Pink, the creative class by R. Florida, and the precariat by G. Standing. Additionally, the author examines the contributions of Zh.T. Toshchenko, a prominent Russian researcher actively refining the theory of the precariat. The article integrates various perspectives to provide a comprehensive theoretical analysis of the socio-professional structure in the context of post-industrialization.Results and discussion. According to researchers conceptualizing its effects, postindustrialization marks the transition to a service economy where knowledge is a key resource and production factor. Creativity, autonomy, and intrinsic motivation are distinctive traits of a significant portion of the modern workforce. At the same time, the socio-professional structure of society reveals a growing divide between intellectual workers, who often prefer flexible employment, and precariat groups, characterized by unstable employment, fluctuating incomes, and an uncertain social position.Conclusion. The destabilization of employment relations has resulted in the emergence of two distinct labor groups with different socio-economic statuses and often opposing values and attitudes toward work: the privileged and the deprived. Members of privileged groups, as described by D. Pink and R. Florida, effectively utilize the opportunities created by labor market transformations, while representatives of deprived groups, examined by G. Standing and Zh.T. Toshchenko, act as a “substitute” for traditional employees, working under unstable conditions and in low-prestige positions.